The Right to Refuse Treatment Based on the Buddhist Ethics - Candiko, Phrakhrupalad Natthaphon (Journal of International Buddhist Studies, 2015)
The Right to Refuse Medical Treatment in line with the Buddhist Ethics aimed at studying the concept and process of refusing the medical treatment in the western and eastern countries and in the concept of Buddhist Ethics. Regarding to the concept of refusing the medical treatment, it has been occurring in the United States of America and other countries. The reject of blood transfusion due to the religious belief, unable to heal due to the high medical expense and living in the desolate society without relatives therefore they refused to the treatment. However, the Thai people have been influenced from abroad as well, but the factors of refuse to treatment were different viz., to help the hopeless patients from their sufferings, to reduce the cost of treatment from the relatives and the will to die or live is the personal freedom. The process of legal right to refuse medical treatment based on the National Health Act, B.E. 2550, it is defined in the Ministerial Regulation Section, 1 on the Rights and Duties of Health Article 12. The statements can be summarized as: persons have right of writing a letter of intent to refuse the medical treatment that is just to prolong life or to end the suffering from illness. If the doctor has followed the letter of intent under paragraph one, he or she is not considered as doing the wrong action. Regarding to the problem analysis on the legal right to refuse medical treatment based on the National Health Act, B.E. 2550, it was found the disagreement about the National Health Act that has vulnerable to implementation, and because there are many invalid aspects based the rules and regulations. However, the Buddhist Ethics presented the idea of right and wrong and the solution of the legal right to refuse medical treatment for 3 stages viz., 1) the Fundamental Buddhist Ethics - Pañcas̵īla or the Five Precepts and Pañcadhamma: the five ennobling virtues, 2) Intermediate Buddhist Ethics- Kusala-kammapatha: whole some course of action and akusala-kammapatha: unwholesome course of action and 3) Advance Buddhist Ethics – Ariyamagga: the Eightfold Noble Path and included the criteria of wholesomeness and unwholesomeness as: 1) intention, 2) Action and 3) Fruition. Therefore, if a person conduct in wrong act of the primarily Buddhist Ethics is considered as the wrong action based on the Buddhist Ethics.